SBA-15 intercalated Mg-Al hydrotalcite: an environmental friendly catalyst for hydroisomerization of olefin - Baskaran, Thangaraj; Christopher, Jayaraj; Ajithkumar, Thalasseril G.; Sakthivel, Ayyamperumal (Applied Catalysis A-General, 2014)
SBA-15 Molecular sieve-intercalated Mg-Al hydrotalcite (MASBA-HT) was synthesized for the first time by a simple straightforward method. The intercalation of SBA-15 molecular sieve between the interlayer of HT was evident from powder XRD, TEM and FT-IR studies. The presence of SBA-15 facilitates retention of the layered structure for first time, even after calcination at high temperature of 550 degrees C. The resultant material possesses moderate acidity which comes from incorporation of aluminum into the framework of SBA-15 and also contained soluble basicity similar to HT materials. The material shows promising activity for hydroisomerization of 1-octene resulting in good substrate conversion (80%) and branched isomers selectivity (45%). The catalytic activity remains constant over longer duration and repeated runs. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Branched alkenes; Hydroisomerization; Intercalated-hydrotalcite; layered materials; Mesoporous SBA-15

Environmentally friendly route for grafting of molybdenum carbonyl onto a diaminosilane-modified SBA-15 molecular sieve and its catalytic behaviour in olefin epoxidation - Baskaran, Thangaraj; Kumaravel, Raju; Christopher, Jayaraj; Ajithkumar, Thalasseril G.; Sakthivel, Ayyamperumal (New Journal of Chemistry, 2015)
A simple route has been established for grafting molybdenum carbonyl onto the surface of a diaminosilane-modified SBA-15 molecular sieve. The successful grafting of the molybdenum carbonyl species onto diamine-functionalized SBA-15 was evident from FT-IR studies. The resultant molybdenum-carbonyl-complex-grafted SBA-15 (SBA-DA-Mo) materials show promising activity for the epoxidation of various olefins with good conversion (90-95%) and the formation of epoxide as the major product. The catalytic activity remains constant over several runs.

Aluminium oxide supported on SBA15 molecular sieves as potential lewis acid catalysts for epoxidering opening using aniline - Yadav, Rekha; Muralidhar, Akhila; Shamna, A.; Aghila, P.; Gurrala, Lakshmiprasad; Sakthivel, Ayyamperumal (Catalysis Letters, 2018)
A series of aluminium oxide (Al2O3)-supported SBA-15 molecular sieves were prepared using a one-step wet-impregnation method. Powder X-ray diffraction, nitrogen adsorption/desorption, infrared spectroscopy and ammonia TPD were used to investigate the structures and chemical natures of the surface-bound species. The FT-IR studies of metal-impregnated SBA-15 materials revealed strong covalent interaction of Al2O3 on SBA-15 materials with strong Lewis acidic properties, evident from ammonia-TPD studies. The metal oxide-supported SBA-15 catalysts are active for epoxide ring opening with aniline at room temperature, and showed remarkably high stability and selectivity towards mono-alkylated products (about 86%) viz., 1-(phenylamino)propan-2-ol and 2-(phenylamino)propan-1-ol. The catalytic activities remained intact after several recycles. The observed activities and selectivities were compared with other metal oxide-loaded SBA-15 catalysts obtained by similar preparation methods. Aluminium oxide supported SBA-15 molecular sieves were prepared using a one-step wet-impregnation method. The materials showed strong Lewis acidic sites and promising catalytic activity for epoxide ring opening with aniline at room temperature.

The ex situ exsolved exsolved Ni-Ru alloy from nickel-ruthenium co-doped SrFeO perovskite as a potential catalyst for C=C and C=O hydrogenation - Bhavisha, Meloth; Balamurugan, Sarkarainadar; Gopinath, Chinnakonda S.; Sakthivel, Ayyamperumal (SUSTAINABLE ENERGY & FUELS, 2024)
Keywords: LIQUID-PHASE HYDROGENATION; OXIDE FUEL-CELLS

Catalytic hydrogenation of cinnamaldehyde over nanocrystalline nickel-doped lanthanum aluminate: synergistic effect of nickel and oxygen vacancies - Bhavisha, Meloth; Balamurugan, Sarkarainadar; Venkatesha, Naragalu J.; Gopinath, Chinnakonda S.; Sakthivel, Ayyamperumal (ChemCatChem, 2025)
Nickel-doped lanthanum aluminium perovskite, LaAl1-xNixO3-delta with x = 0, 0.1, 0.2, 0.3, 0.4,0.5, 0.6, and 0.75 (LANx), were obtained through a combustion method followed by a calcination process. The obtained LANx materials crystallized in the cubic structure by the Pm-3m (221) space group. The nanocrystalline nature of the LANx materials was confirmed by the average crystalline size determined using Debye-Scherrer formula. X-ray photoelectron spectroscopy (XPS) studies showed that nickel was present in the +2 and +3 oxidation states. The introduction of nickel resulted in distinct peaks in TPR in the temperature range of 200-600 degrees C, with an enhanced reducibility of the materials. The LANx materials were thoroughly assessed for their effectiveness in the hydrogenation of cinnamaldehyde. The maximum catalytic activity (cinnamaldehyde conversion of 98% with a hydrocinnamylalcohol selectivity 96.5%) was observed with the presence of the LAN7 catalyst at 150 degrees C for 6 h at a H2 pressure of 10 bar. The catalytic activity is maintained even after four cycles, which broadens the application scope as the material is sustainable, scalable, cost-effective, and a potential alternative to reported noble metal catalysts. The synergistic effect of nickel and oxygen vacancies in the catalyst improves the reducibility and provides a promising catalytic activity in the cinnamaldehyde hydrogenation.
Keywords: Cinnamaldehyde; Hydrocinnamylalcohol; Hydrogenation; Nickel; Perovskite oxide